Agricultural science and technology policy for growth and poverty reduction - Omamo, Steven Were; Naseem, Anwar (International Food Policy Research Institute, 2005)
This paper argues that the largely unrealized potential of agricultural science and technology (S&T) in promoting growth and poverty reduction in developing countries results from deeply rooted incompatibility among policy environments, institutional arrangements, and micro conditions and behavior in agricultural research and development (R&D). Achieving growth and poverty reduction based on greater agricultural productivity therefore means achieving greater compatibility among these three dimensions of agricultural innovation systems. Research is sorely needed to build understanding of (1) the “big picture” influencing agricultural S&T policy design and implementation in developing countries, (2) strategies for sustainable funding and delivery of agricultural R&D, (3) priorities for and impacts of emerging and prospective agricultural technologies, and (4) the role of science in food and agricultural policy processes. Agricultural S&T policy analysis as presented here extends beyond the current boundaries of agricultural economics into such disciplines as public finance, public administration, political science, history, sociology, and psychology. The economics of science and innovation in industry has embraced some of these disciplines and benefited greatly from having done so, as has industrial policy in the developed world. The fundamental horizontality of agricultural development policy and the long reach of agricultural S&T policy suggest similarly high returns were agricultural economics to do the same for science and innovation in agriculture.--Author's Abstract